(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Inventory is equipment or goods contained in an agency that is used to support an agency or submitted as a service to the community. This study aims to determine whether the application of inventory accounting treatment in the pharmaceutical industry is in accordance with PSAP No. 5. This study uses a descriptive qualitative method, which analyzes the application of inventory accounting treatment in the form of secondary data obtained from the Health Office, and compares it with the Statement of Government Accounting Standards No. 5. The results showed that the application of inventory accounting treatment at the Health Office was in accordance with PSAP No. 5. It can be seen in terms of classification, recognition, measurement, disclosure and presentation, and inventory expenses, all of which are in accordance with PSAP No.5.